Image and the UN image discourse - Шугаєв, Андрій Володимирович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The research of international institutions’ image and verbal means of its representation is rather topical in modern linguistics. A special attention is dedicated to the mass-media as the instrument of information explication. The article focuses on the image discourse analysis, UN image representation in mass-media and features of image discourse. Moreover, a correlation of mass-media with the UN image formation is researched. The article deals with the research of the notion "image". The linguistic peculiarity of media texts that forms the image of international organizations, such as the UN needs the detailed investigation illustrated on the basis of the relevant linguistic material. It is proved that a notion "image" has a Latin origin (illustration, reflection, visibility) related to the word imitare that means "imitate".